Error performance and energy efficiency analyses of fully cooperative OFDM communication in frequency selective fading. Issue 18 (1st December 2016) - Tran, Le Chung; Mertins, Alfred
Abstract : This study devises for the first time a comprehensive analysis of decode‐and‐forward, space–time coded, fully cooperative orthogonal frequency division multiplexing (OFDM) systems from both error performance and energy efficiency perspectives, in either identically or non‐identically distributed frequency selective Rayleigh fading channels. The authors' analyses show the interesting result that the fully cooperative OFDM is better than direct OFDM transmission from both perspectives in many cases, especially at a low power and low signal‐to‐noise ratio regime, making it particularly useful for emerging low power applications, such as wireless body area networks.